PERAN TAKMIR DALAM MENINGKATKAN KEMAKMURAN MASJID (STUDI KASUS DI MASJID AL-HUDA CITRODIWANGSAN LUMAJANG) - Sa'adatu Mukarromatil Arifah; indana zulfa (Dakwatuna: Jurnal Dakwah dan Komunikasi Islam, 2018)
Al-Huda Mosque, in Dewi Sartika street no.01, carries outsome constructive activities. The mosque takmir always strives to improve the advancement of the mosque. The focus of this study is the role of the mosquetakmir in increasing mosque prosperity in terms of idarah, imarah, and ri'ayah. This study employs qualitative methods with a case study approach. The conclusions of this study are as follows: First, the roles of takmir in increasing mosque prosperity in terms of idarah, among others, are planning a program ofworkingcompetently; forming the mosque management through a deliberation; running administration role effectively. Second, the roles of takmir in increasing the prosperity of the mosque in terms of imarah, among others, are holding magdzoh and gairu magdzoh; organizing Islamic education and teaching; organizing da'wah; holding social activities. Third, the roles of takmir in increasing the prosperity of the mosque in terms of ri'ayah among others, are completing mosque facilities and infrastructure; maintaining cleanliness, attractiveness, and security of the mosque; maintaining the appearance of the mosque. Key Words: the Role of Takmir, Mosque Prosperity, Idarah, Imarah, Ri’ayah